2007
DOI: 10.2298/zmspn0713093s
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of toxigenic Fusarium species and fusariotoxins in wheat grain in Serbia

Abstract: A total of 88 and 40 wheat samples collected immediately prior to harvest in 2005 and 2006, respectively, under different agroecological conditions, were studied in respect to the occurrence of Fusarium spp. and the production of fusariotoxins. The greatest number of samples was infected with species of the genera Fusarium (81.8 and 65.0%), and Alternaria (36.3 and 17.5%) with the intensity ranging from 9.4 to 84.0% in 2005 and from 23.4 to 80.6% in 2006. Out of 13 identified species belonging to the genus Fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…Additionally, positive and significant correlations between the level of contamination of samples by total fungal counts and the moisture content were found in all of exmined regions (r = 0.475). The results of the mycoflora analysis carried out in this study are similar to previous results found by other Serbian authors (Stanković et al 2007;Milićević 2008). This shows that the incidence of these various species was important, as the produce was stored for prolonged periods of time.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, positive and significant correlations between the level of contamination of samples by total fungal counts and the moisture content were found in all of exmined regions (r = 0.475). The results of the mycoflora analysis carried out in this study are similar to previous results found by other Serbian authors (Stanković et al 2007;Milićević 2008). This shows that the incidence of these various species was important, as the produce was stored for prolonged periods of time.…”
Section: Resultssupporting
confidence: 91%
“…DON was detected in the highest concentration (1988.1 μg kg -1 ), followed by FB 1 (882.7 μg kg -1 ), ZEA (442.6 μg kg -1 ) and T-2 (24.2 μg kg -1 ). These results have been expected, considering that results obtained in previous studies showed that samples originating from wheat grain contained high concentrations of mycotoxins (Stojanović et al, 2005;Stanković et al, 2007). High concentrations of fusariotoxins in wheat grain can be explained by a high frequency of producers of these mycotoxins in Serbia (Lević et al, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…Results on wheat grain contamination by ZEA over years and localities in Serbia point to effects of climatic factors on the production of mycotoxins. According to results obtained by Stanković et al (2007), ZEA was detected in samples of wheat grain in the range of 37 to 331 μg kg -1 , in 64.5% samples. The presence of ZEA was mainly detected in the three wheat varieties most often grown in Serbia (Evropa-90, Pobeda and Renesansa) (Stojanović et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…They are predominantly associated with Fusarium Head Blight in wheat and other cereals all over Europe [59]. Fusarium species synthesise a wide range of mycotoxins of diverse structure and chemistry, comprising trichothecenes (T-2 toxin, HT-2 toxin, diacetoxyscirpenol (DAS), deoxynivalenol (DON), DON-3-glucoside (DON-3-Glc), 15- and 3-acetyl-deoxynivalenol (ADONs), nivalenol (NIV) and fusarenon-X (FUS-X)), zearalenone (ZEN) and fumonisins (FUMs) [60].…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
“…Only one research was conducted on the presence of DAS in Serbia [59]. It was found in 9 out of 31 samples of crop wheat (29%), in the range of 31.0–125.0 μg kg −1 and with a mean value for positive samples of 61.0 μg kg −1 and the median value of a 62.0 μg kg −1 .…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%